CoRep Meeting Gothenburg 10 July 2018 - (:unkn) unknown (AESOP, 2018)
AGENDA AESOP Council of Representatives Meeting Chalmers University of Technology 10th July 2018 9:30 1. Approval of the Agenda (AG, PP) F 2. Approval of the CoRep Meeting Minutes and Resolutions from Newcastle (AG, PP) F 3. Progress report on the 2019 Venice Congress (ZNB) F 4. Election of the host of the 2019 HoS Meeting (PP) F a. University of Ljubljana 5. Election of AESOP Secretary General (PP) F 6. Ratification of AESOP membership (PP) F a. Department of Architecture (University of Coimbra) as Associate Member b. Department of Safety, Economics, and Planning (University of Stavanger) as Full Member c. Urban Studies (University of Washington Tacoma) as Corresponding Member d.Mohamed Alaa Mandour, Individual Member 11:00 – 11:15 Coffee Break 7. Financial Matters (BB) F 8. Quality Recognition Report (DG) F 9. GPEAN & UN Habitat Update Report (EBS) F 10. Transactions of AESOP Report (EBS) F 11. YA Network Report (ADK) F 12:30 – 14:00 Lunch Break 12. AESOP Lecture Series (PP) 13. AESOP Awards (PP) 14. AESOP-ACSP Collaboration (ZNB, BD) 15. AEKOM (AESOP KnOwledge Management and Sharing platform) 16. AOB This item contains the following files: agenda-for-the-corep-meeting-10th-july-gothenburg-29-06-2018.pdf application-for-associate-membership-university-of-coimbra-department-of-architecture-03-07-2018.pdf application-for-corresponding-membership-university-of-washington-tacoma-urban-studies-03-07-2018.pdf application-for-full-membership-university-of-stavanger-department-of-safety-economics-and-planning-03-07-2018.pdf application-for-hosting-the-2019-hos-meeting-29-06-2018.pdf application-for-individual-membership-mandour-mohamed-alaa-03-07-2018.pdf application-for-secretary-general-29-06-2018.pdf gpean-report-04-07-2018.pdf minutes-of-the-corep-meeting-in-newcastle-19th-april-2018-29-06-2018.pdf resolutions-of-the-corep-meeting-in-newcastle-19th-april-2018-29-06-2018.pdf review-of-application-for-associate-membership-university-of-coimbra-department-of-architecture-03-07-2018.pdf review-of-application-for-associate-membership-university-of-coimbra-department-of-architecture-03-07-2018 (1).pdf review-of-application-for-or-full-membership-university-of-stavanger-department-of-safety-economics-andplanning-04-07-2018.pdf review-of-application-for-or-full-membership-university-of-stavanger-department-of-safety-economics-andplanning-08-07-2018.pdf transactions-call-for-papers-04-07-2018.pdf transactions-editorial-of-issue-2-04-07-2018.pdf transactions-progress-report-04-07-2018.pdf ya-corep-activity-financial-report-08-07-2018.docx
Keywords: Gothenburg; CoRep meeting; material; 2018